Sofrimento psíquico e síndrome de Burnout: um estudo com professores do PPGE/CE/UFSM - Pimenta, Alessandra Giuliani (2004)
This scientific study follows the Search Line of Teachers from the Post-Graduation Program on Education and it is based on the investigation and identification of the subjective experience of the psychological pressure on teachers of the PPGE/CE/UFSM, and its straight relationship with the Burnout Syndrome. The theme choice was originated from the difficulties observed in the daily activities of these professionals facing the countless demands they are imposed, and their real labor conditions contradictory and complex day after day. Taking into consideration the aspects that characterize this crisis (of educators identity and the education itself) the affective character has been pointed out, inherent to the activity evidenced by the straight bond established between teachers and students. In this way, it has been consolidated as an approach of extreme prominence, since they get vulnerable to the continuous difficulties and feel their emotional resistance influencing negatively the pedagogic practice and, in some situations, provoking the incidence of the burnout, which is divided in three dimensions: Emotional Exhaustion (EE), Personal Realization at Work (PR) and Depersonalization (DE). It corresponds to an occupational syndrome, where there is an exhaustion of the vital energy caused by the daily stress that professors are submitted and by the interpersonal involvement attempted. A descriptive-interpretative investigation of a quantity-qualitative nature was carried out using the MBI-ED instrument (Maslach Burnout Inventory Educators Survey), considered as one of the best instruments to detect the burnout degree in the professionals of the area. The analysis of the results, showed that ≈27% of the professors has manifested representative index to burnout or for some of its dimensions. From these, ≈55% revealed high level for EE, ≈41% low level for PR, and ≈36% high DE. The results confirmed that the peculiarity on this level of teaching favored the incidence of the Burnout Syndrome and only by the knowledge of the causes, it will be possible to elaborate efficient strategies of intervention and the solution for this problem.